Synthese und biologische Evaluierung Sterolmodifizierter Hedgehog-Signalpeptide und Proteine - Peters, Carsten (Universität Dortmund, 2003)
The Hedghog (Hh) family of signalling molecules are key players in patterning numerous types of tissues. Mutations in Hh and its downstream signalling molecules are also associated with numerous oncogenic and disease states. The Hh family of molecules are secreted proteins that undergo several post-translational modifications gaining full activity. Hh molecules undergo a maturation process in which they autocatalytically cleave, generating an N-terminal polypeptide (Hh-Np) containing all the signalling functions, and a C-terminal polypeptide appearing to have no function than catalysing the autoproteolytic cleavage. During this cleavage process, a cholesterol moiety is attached covalently via an ester function to the C-terminal glycine of the signalling domain. Furthermore the hydrophobicity of the protein is increase by the addition of an palmitic acid residue to the cysteine immediately following the peptide cleavage site. To evaluate membrane binding properties of cholesterol, different sterol modified peptides were synthesized by means of solid phase peptide chemistry. With these peptide membrane binding properties were examined in vitro using fluorescence spectroscopy. To mimic the situation in vivo constructs that consist of truncated N-Ras protein and sterol modified peptides were generated by MIC-ligation. With these constructs membrane binding properties of different sterol modified proteins were determined in vivo and in vitro.
Keywords: Hedgehog; Signaltransduktion; Proteine; Lipidierte Proteine; 540